Characteristics of travel insurance market and the ways to increase its volume in Russia - Novichkov I. S. (Interactive science, 2017)
this article presents the study of the Russian and foreign insurance practices, outlines options for increasing the volume of the market, as well as suppressing the psychological barrier of the Russian tourists.
Keywords: туризм; страхование; потребление; услуги; services; Tourism; consumption; insurance; курортные зоны; страховые риски; resort areas; insurance risks